Persepsi Siswa terhadap Pembelajaran Al-Qur'an (Tahsin/Tajwid) dalam Meningkatkan Kemampuan Membaca di Madrasah Diniyah Nurul Huda Bngodua Cirebon - Nurlaeli Nurlaeli (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
This study aims to investigate students' perceptions of Qur'an learning (Tahsin and Tajwid) in improving their Qur'an recitation skills at Madrasah Diniyah Nurul Huda Bangodua, Cirebon. This study employed a qualitative approach using a descriptive method. The research participants consisted of 10 fourth-grade students and one teacher responsible for Qur'an learning. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings indicate that students have positive perceptions of Tahsin and Tajwid learning. The learning process helps students improve the pronunciation (makhraj) of Arabic letters, understand the rules of Tajwid, enhance the fluency of Qur'an recitation, and develop greater confidence in reading the Qur'an. Supporting factors contributing to the success of the learning process include the talaqqi method, direct guidance from the teacher, and a conducive learning environment. The challenges faced by students include limited instructional time, difficulty distinguishing certain Tajwid rules, and insufficient practice in reading the Qur'an at home. Overall, Tahsin and Tajwid instruction plays a significant role in improving students' Qur'an recitation skills at Madrasah Diniyah Nurul Huda Bangodua, Cirebon.